Numerical modeling of the low cycle fatigue: effect of manufacturing imperfections caused by machining process - Abarkan Ikram (EDP Sciences, 2021)
The majority of mechanical components in nuclear power plants must be designed to withstand extreme cyclic loading conditions. In fact, when these components are subjected to low cycle fatigue, machining imperfections are considered one of the most significant factors limiting their service life. In the present work, using finite element analysis, a methodology has been suggested to predict the fatigue life of cylindrical parts made of 316 SS, at ambient temperature, under nominal strain amplitude ranging from ± 0.5 to ±1.2% with various surface roughness conditions. Two different multiaxial strain-life criteria have been considered to estimate the fatigue life, namely Brown-Miller and maximum shear strain. The comparison between the predicted and the experimental fatigue lifetimes has revealed that the adopted multiaxial strain life criteria can successfully estimate the fatigue life of 316 SS grade under uniaxial loading conditions. Furthermore, it has been found that the fatigue life decreases as the surface roughness average value increases, which indicates that surface regularities have a significant impact on low cycle fatigue life. Therefore, the proposed methodology is found to be capable of assessing the impact of surface roughness on the fatigue life of this specific steel in the low cycle fatigue regime.